2010
DOI: 10.1111/j.1467-6435.2010.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Health or Happiness? What Is the Impact of Physical Activity on the Individual?

Abstract: This paper models the effect that physical activity such as sports participation and active travel, through walking and cycling, has on self-reported health and well-being. The results show that physical activity and active travel mainly have a positive effect on both individual health and well-being. Although, cycling has health benefits, it also appears to involve some disutility, which requires further investigation. Copyright � 2010 Blackwell Publishing Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 59 publications
(77 reference statements)
7
105
0
5
Order By: Relevance
“…Theoretically, one might argue that an ordered measurement of SWB and binary covariates would be most suitable. However, the SWB research has shown that the choice of estimator is not of significance in the findings [17,36]. There are other advantages too.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Theoretically, one might argue that an ordered measurement of SWB and binary covariates would be most suitable. However, the SWB research has shown that the choice of estimator is not of significance in the findings [17,36]. There are other advantages too.…”
Section: Methodsmentioning
confidence: 99%
“…[36], there is no study that investigates whether the magnitude of this impact is age-specific, although, it is also well known that sport participation is strongly influenced by age [5,12,24,33]. Consequently, this paper seeks to make a unique contribution to the existing literature by exploring the age-specific effects of sports participation on SWB for a broad cross-section of 19 European countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While growing evidence exists that sports participation increases SWB (e.g., [12,14]), there is no study that investigates whether the magnitude of this impact is agespecific. This is surprising since, as mentioned above, sports participation and engagement in physical activity have a strong age-specific profile.…”
Section: Contribution To This Volumementioning
confidence: 99%